(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper aims to analyze diverse images with a special semantic density to express the different ways of journey to the Other World among the peoples of Romano-Celtic Hispania, namely the transit over water and through the air. These iconographies are alternative to the HellenisticoRoman koiné, corresponding to a moment of cultural change, and have to be already considered within the Roman provincial contex.